THE COMPARISON OF THE PERFORMANCE OF ISLAMIC COMMERCIAL BANKS BEFORE AND DURING THE COVID-19 PANDEMIC - Restu Frida Utami; Makhrus Makhrus (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
The World Bank estimates that the global economic outlook during the COVID-19 pandemic will change and have an impact on the short and long term. Monetary policy supports a reduction in the recession caused by the Covid-19 pandemic. Islamic banks with good financial performance will be able to carry out their functions properly. comparing the current ratio with the past can be used as a predictive tool for banking in the future. This study analyzes the comparison of financial performance before and during the covid-19 pandemic using the following ratios: ROA, FDR, NPF, BOPO. The research is a comparative research. The sample in this study were 14 Islamic Commercial Banks. The research data is in the form of secondary data, namely quarterly financial ratio. The data analysis method uses the normality test and the difference test. The results of the study are that there is no difference in the performance of ROA, FDR, NPF and BOPO between before the 2019 pandemic and when the covid 19 pandemic occurred in 2020. Sharia banking during the Covid 19 pandemic in 2020 still performed well because it had a performance predicate that was not worse than in 2020.